2022
DOI: 10.1109/access.2022.3163292
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Arabic Text Summarization

Abstract: The explosion of online and offline data has changed how we gather, evaluate, and understand data. It is frequently difficult and time-consuming to comprehend large text documents and extract crucial information from them. Text summarization techniques address the mentioned problems by compressing long texts while retaining their essential contents. These techniques rely on the fast delivery of filtered, high-quality content to their users. Due to the massive amounts of data generated by technology and various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…The experimental result of the proposed model for abstractive text summarization using evaluation metrics Rouge1, Rouge2, Rouge-l, Bleu, and Arabic Rouge for the EASC dataset was 0.587, 0.48, 0.56, 0.42, and 0.652, while for the HASD dataset, they were 0.6374, 0.4908, 0.6047, 0.44, and 0.713 As shown in tables (16and17). As shown in table (19), we compare our proposed system to other abstract Arabic summarizations that use deep learning. When we compare our proposed system to those from other research studies, we nd that ours has the highest levels of Rouge1, Rouge2, Rouge-l, and Bleu, which means that its summary is the best.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental result of the proposed model for abstractive text summarization using evaluation metrics Rouge1, Rouge2, Rouge-l, Bleu, and Arabic Rouge for the EASC dataset was 0.587, 0.48, 0.56, 0.42, and 0.652, while for the HASD dataset, they were 0.6374, 0.4908, 0.6047, 0.44, and 0.713 As shown in tables (16and17). As shown in table (19), we compare our proposed system to other abstract Arabic summarizations that use deep learning. When we compare our proposed system to those from other research studies, we nd that ours has the highest levels of Rouge1, Rouge2, Rouge-l, and Bleu, which means that its summary is the best.…”
Section: Discussionmentioning
confidence: 99%
“…Many methods were applied, and different document types, including web pages, Wikipedia pages, and reviews. Many Arabic datasets for document summarization research were found in the reviewed literature, such as EASC [35] and ANT [16]; also, Elsaid et al [5] stated in their comprehensive review the availability of 13 Arabic news datasets created for document summarization. Yet, no Arabic dataset was found that targets Arabic review summarization research.…”
Section: Related Workmentioning
confidence: 99%
“…ATS aims to produce a smooth and short summary that includes important information from the original text [2]. Several studies addressed ATS for English documents [3,4]; however, fewer studies are available for the Arabic language due to its rich morphological structure, the range of dialects, and the scarcity of data and tools [5]. Arabic is the fifth most spoken language globally, with more than 400 million speakers worldwide [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations